The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/00004728-200605000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Changes in a Tumor and Peritumoral Tissue After Stereotactic Irradiation for Brain Tumors

Abstract: Changes in nADC as measured by diffusion-weighted imaging can predict response to STI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In our study, the ADC values corresponded to the histopathologic rate of necrosis within the tumors, sug gesting that diffusion-weighted imaging has a potential for early detection of tumor necrosis after TACE, which is in agreement with the findings in theoretical diffusion models and in vitro and in vivo studies [3,[5][6][7]11] . DWI can differentiate viable and necrotic tissues by calculating ADC values because in the former, cell and intracellular membranes are intact, restricting molecular diffusion into viable tumors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the ADC values corresponded to the histopathologic rate of necrosis within the tumors, sug gesting that diffusion-weighted imaging has a potential for early detection of tumor necrosis after TACE, which is in agreement with the findings in theoretical diffusion models and in vitro and in vivo studies [3,[5][6][7]11] . DWI can differentiate viable and necrotic tissues by calculating ADC values because in the former, cell and intracellular membranes are intact, restricting molecular diffusion into viable tumors.…”
Section: Discussionsupporting
confidence: 89%
“…The sensitivity of diffusion-weighted imaging to water motion can be varied by changing b value, which is a function of diffusion gradient strength, duration of the gradient, and interval between diffusion gradients. Diffusion-weighted imaging has been used to predict and monitor the effect of several treatment options and to differentiate between viable and necrotic tumor tissues [3][4][5][6][7] . In these studies, a variety of b values ranging from 0 s/mm 2 to 4000 s/mm 2 were used [3][4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different modalities of early-stage follow-up examination, such as contrast-enhanced CT [8] and fluorodeoxyglucose positron emission tomography (FDG-PET), have been of great interest and their usefulness has been reported by several groups [9,10]. Another approach -MR diffusion-weighted imaging (DWI) -which is based on the measurement of motion of water molecules, has also been reported as a non-invasive evaluation modality [11][12][13][14][15][16][17][18][19]. In this method, the apparent diffusion coefficient (ADC) represents the water content and distribution, the cellular density and the cell membrane integrity, suggesting the potential usefulness of an ADC map for estimating tumour viability.…”
mentioning
confidence: 99%
“…In this method, the apparent diffusion coefficient (ADC) represents the water content and distribution, the cellular density and the cell membrane integrity, suggesting the potential usefulness of an ADC map for estimating tumour viability. Indeed, DWI has been successfully used to assess the efficacy of radiotherapy [11,12], chemotherapy [13][14][15] and transcatheter arterial embolisation [16,17]. To our knowledge, only two studies have reported the use of DWI to evaluate the therapeutic outcome of RFA [18,19].…”
mentioning
confidence: 99%